Human Resource Management in Efforts to Improve School Quality (Study at Nur El Falah Kubang High School and 1 Petir High School, Serang District) - Fiki Syururoh; Eneng Muslihah; Encep Syarifudin (PT FORMOSA CENDEKIA GLOBAL, 2022)
The formulation of the problem in this research is how to implement human resources and what are the inhibiting factors and supporting factors for human resource management at Nur El Falah Kubang High School and SMAN 1 Petir, Serang district in an effort to improve school quality? The purpose of this research is to find out the implementation of human resources and to find out what are the inhibiting factors and supporting factors for human resource management in an effort to improve school quality at Nur El Falah Kubang High School and 1 Petir State Senior High School, Serang district. And the benefit of this research is to find out how and to what extent human resource management is in an effort to improve school quality. The main issues in this study are: planning, organizing, human resource planning, supervision in improving school quality at Nur El Falah Kubang High School and SMA Negeri 1 Lightning, Serang district. To obtain an overview of the correlation, the type of research chosen is qualitative research using qualitative research methods. This research was conducted at Nur El Falah Kubang High School and 1 Petir State Senior High School, Serang Regency, Serang Regency. The population in this study is homogeneous or consists of several types.